Mapping the Landscape of Affirmative Healthcare for Transgender Communities through Bibliometric Analysis - Ashwani Dubey; Papia Raj (Jurnal Kesehatan Masyarakat, 2025)
Gender-affirmative healthcare provides a supportive and safe space for individuals irrespective of their gender identity. Despite this, transgender individuals encounter discrimination when seeking equitable healthcare. Consequently, this research aims to examine the current state of transgender healthcare research and identify areas requiring further investigation. Employing the Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA), the study initially identified 278 articles, with 48 meeting the inclusion criteria for analysis. Bibliometric analysis was conducted using Biblioshiny and Vos-viewer software. The review underscores the growing academic interest in gender affirmative care and emphasizes the necessity for increased scholarly focus. Analysis of document production by various countries reveals an uneven geographical distribution of research in this area. Additionally, the study identifies a trend towards a greater emphasis on affirmative approaches in addressing health disparities through term co-occurrence analysis, while thematic analysis emphasizes the importance of comprehensive adoption of gender-affirmative practices. This research holds potential in informing the development of inclusive policies and comprehensive strategies to improve the health outcomes of transgender populations, thus advancing health equity and contributing to the achievement of Sustainable Development Goals.